2022
DOI: 10.1186/s12920-022-01241-9
|View full text |Cite
|
Sign up to set email alerts
|

Identifying key genes and functionally enriched pathways in Th2-high asthma by weighted gene co-expression network analysis

Abstract: Background Asthma is a chronic lung disease characterized by reversible inflammation of the airways. The imbalance of Th1/Th2 cells plays a significant role in the mechanisms of asthma. The aim of this study was to identify asthma-related key genes and functionally enriched pathways in a Th2-high group by using weighted gene coexpression network analysis (WGCNA). Methods The gene expression profiles of GSE4302, which included 42 asthma patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…A recent study explored the relationship between COPD and blood eosinophil count and airway epithelial transcriptome, showing that CST1 was the only gene positively associated with blood eosinophil count in asthma and COPD patients ( 68 ). CST1 is highly expressed in the airway epithelium of Th2-high asthma patients, and is one of the biomarkers to distinguish Th2-high from Th2-low asthma ( 69 ). These findings indicate that CST1 plays a key role in the pathogenesis of asthma and CRSwNP, and is a key biomarker linking CRSwNP and asthma.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study explored the relationship between COPD and blood eosinophil count and airway epithelial transcriptome, showing that CST1 was the only gene positively associated with blood eosinophil count in asthma and COPD patients ( 68 ). CST1 is highly expressed in the airway epithelium of Th2-high asthma patients, and is one of the biomarkers to distinguish Th2-high from Th2-low asthma ( 69 ). These findings indicate that CST1 plays a key role in the pathogenesis of asthma and CRSwNP, and is a key biomarker linking CRSwNP and asthma.…”
Section: Discussionmentioning
confidence: 99%
“…LASSO identified potential DCEGs includes CPA3, SERPINB2, CHCHD5, EMC6, RPUSD3, POSTN, SEC14L1 and UPK1B in AECs dataset and these DCEGs were also persistently upregulated in multiple tissue/cell type datasets from asthmatic subjects. The previous study reported that elevated expression of CPA3 gene was observed in asthmatic subjects compared to controls and CPA3 gene correlated with sputum mast cells, asthma and rhinitis 42 . Recent study reported that the expression level of SERPINB2 gene was increased in airway epithelial cells of asthmatic and in atopic asthmatic subjects compared controls 43 .…”
Section: Discussionmentioning
confidence: 93%
“…CEACAM5 is an IL-13-regulated epithelial gene that is upregulated in severe asthma and associated with increased asthma exacerbations 44 46 . It has also been previously identified as a hub gene in a limited microarray-based analysis in 42 cases and 28 controls 47 . Carboxypeptidase A3 (CPA3) is a mast cell (MC) protease and there is a well-known switching of MCs expressing tryptase only (MC T ) to MCs expressing tryptase, chymase and CPA3 (MC TC ) with a dominant expansion of the latter in airways of asthma cases and more specifically in the context of severe asthma 48 .…”
Section: Discussionmentioning
confidence: 97%